Impacts of in-kind transfer to household’s budget proportion: Evidence from early reformation in Indonesia - Girik-Allo, Albertus; Rahayu, Yuyun Puji; Sukartini, Ni Made (Journal of Economics, Business, and Accountancy Ventura, 2016)
The program distributing rice for reducing poverty for poor household (also known as Raskin) is one of social safety net programs in Indonesian’s government with its subsidized rice to the poor. The purpose of this program is to lessen the financial burden of the targeted households and increase food sustainability at the household level. This paper’s aim is to investigate how the effect of in-kind transfer towards the Raskin program over the household’s budgets proportion. This study used Indonesia Family Life Survey (IFLS) data wave 3 (2000) and wave 4 (2007), with the households level as unit analysis. Estimation strategy is applying regression with data panel in fixed effect model (FEM) and instrumental variable (IV). The result shows that the in-kind transfer program is not work for lessening the household’s burden, but in fact has increased the household expenditure, particularly for buying some food. It was found that during the program implementation, there was a significant increase in informal labor wages in Indonesia. Therefore, for typical household who experiencing higher wage income relatives to rice expenditure, will result in total budgets for rice will also increase significantly. In this case, we could conclude that rice is still being normal goods for Indonesia..